2012
DOI: 10.1073/pnas.1204453109
|View full text |Cite
|
Sign up to set email alerts
|

Very high-temperature impact melt products as evidence for cosmic airbursts and impacts 12,900 years ago

Abstract: It has been proposed that fragments of an asteroid or comet impacted Earth, deposited silica-and iron-rich microspherules and other proxies across several continents, and triggered the Younger Dryas cooling episode 12,900 years ago. Although many independent groups have confirmed the impact evidence, the hypothesis remains controversial because some groups have failed to do so. We examined sediment sequences from 18 dated Younger Dryas boundary (YDB) sites across three continents (North America, Europe, and As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
177
5
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(236 citation statements)
references
References 33 publications
(46 reference statements)
14
177
5
2
Order By: Relevance
“…The proposed impact deposited the YDB layer, which contains many cosmic-impact proxies, including magnetic and glassy impact spherules, iridium, fullerenes, carbon spherules, glass-like carbon, charcoal, and aciniform carbon, a form of soot (Firestone et al 2007;Wittke et al 2013). In North America and the Middle East, Bunch et al (2012) identified YDB melt-glass that formed at high temperatures (1730Њ to 12200ЊC), as also reported by three independent groups, Mahaney et al (2010) in South America and Fayek et al (2012) and Wu et al (2013) in North America. This study focuses solely on nanodiamonds (NDs), and so, for independent discussions of other proxies, see Haynes et al (2010) and Paquay et al (2009), who found no evidence for the platinum-group elements iridium or osmium.…”
Section: Introductionmentioning
confidence: 53%
See 3 more Smart Citations
“…The proposed impact deposited the YDB layer, which contains many cosmic-impact proxies, including magnetic and glassy impact spherules, iridium, fullerenes, carbon spherules, glass-like carbon, charcoal, and aciniform carbon, a form of soot (Firestone et al 2007;Wittke et al 2013). In North America and the Middle East, Bunch et al (2012) identified YDB melt-glass that formed at high temperatures (1730Њ to 12200ЊC), as also reported by three independent groups, Mahaney et al (2010) in South America and Fayek et al (2012) and Wu et al (2013) in North America. This study focuses solely on nanodiamonds (NDs), and so, for independent discussions of other proxies, see Haynes et al (2010) and Paquay et al (2009), who found no evidence for the platinum-group elements iridium or osmium.…”
Section: Introductionmentioning
confidence: 53%
“…Details on site setting, geological information, and dating are in tables D2, D3. More details for most sites are in Bunch et al (2012) and Wittke et al (2013). Dating and Age-Depth Models.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To examine this discrepancy, we conducted an independent blind investigation of two sites common to both studies, and a third site investigated only by Surovell Firestone et al) proposed that a cosmic impact event occurred at the onset of the Younger Dryas (YD) cooling episode at about 12,900 calendar years Before Present (12.9 ka B.P.). Evidence cited to support their hypothesis includes elevated levels of iron-and silica-rich magnetic spherules, magnetic grains, iridium, and other materials such as nanodiamonds and high temperature melt glass, in association with proxies indicative of biomass burning (1)(2)(3)(4)(5). Also reported were charcoal, carbon spherules, aciniform soot, and glass-like carbon.…”
mentioning
confidence: 97%